Trauma-Informed Interventions for At-Risk and Justice-Involved Youth: A Meta-Analysis - Olaghere, Ajima (Criminal justice and behavior, 2021)
The impact of trauma on children and youth has potentially serious and long-lasting negative consequences, including increased involvement in the juvenile and criminal justice systems. The objective of this study was to meta-analyze research on the effectiveness of trauma-informed treatment programs for justice-involved youth and youth at risk of justice system involvement who have experienced some form of trauma. Our systematic search identified 29 publications that met our eligibility criteria and represent 30 treatment–comparison contrasts. Six of these evaluated the effectiveness of trauma-informed programs for justice-involved youth, and the remaining 24 evaluated programs for at-risk children and youth. The findings suggest that cognitive-behavioral therapy (CBT), including trauma-focused CBT, is effective. In addition, there was weak evidence suggesting that programs that used a cognitive restructuring component or had the participant create a trauma narrative were slightly more effective than programs without these features. Additional high-quality randomized controlled trials are needed.